THE INFLUENCE OF GOOD CORPORATE GOVERNANCE AND PROFITABILITY TO TAX AVOIDANCE : (A CASE STUDY IN A MINING COMPANY REGISTERED IN INDONESIA STOCK EXCHANGE (IDX)) 2015-2019 - Bagus, Agus Mauludin (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to determine Good Corporate Governance, Profitability and tax avoidance in mining companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. The method used in this study is a verification and descriptive method with a quantitative approach. The variables in this study were measured using a ratio scale, namely quantitative data in the form of numbers. The variables in question are Independent Board of Commissioners, Managerial Ownership, Institutional Ownership and Profitability. The population that is the object of this research includes all financial statements of mining companies listed on the Indonesia Stock Exchange. The samples taken for this study were 5 financial reporting periods from 6 mining companies according to the research criteria. The analysis used is panel data regression analysis, while the hypothesis is tested by t-test and F-test. The results show that the Independent Board of Commissioners, Managerial Ownership, Institutional Ownership and Profitability have a significant effect on Tax Avoidance, with a coefficient of determination of 0.475. While the remaining 52.5% is influenced by other factors not observed in this study.